DIGITAL MARKETING, KUALITAS PRODUK DAN KERAGAMAN PRODUK DALAM MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA TOKO MARKAS BELI DI SHOPEE DENGAN MODERASI VARIABEL KEPERCAYAAN - Astutik, Wiji; Ediyanto, Ediyanto; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
In today's rapidly evolving digital era, consumer shopping behavior has shifted significantly, with e-commerce emerging as a key platform for fulfilling consumer needs. This study aims to analyze and examine the impact of digital marketing, product quality, and product diversity on consumer purchase decisions, with trust as a moderating variable. Adopting an explanatory research, the population in this study consists of consumers of the Markas Beli Store. The sampling technique used in this study is simple random sampling. Data analysis and hypothesis testing were conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of the direct effect hypothesis testing, conducted using the SmartPLS 3.0 application, show that digital marketing has a weakening effect on the positive relationship with purchase decisions. Similarly, product quality also weakens the positive relationship with purchase decisions. In contrast, product diversity significantly strengthens the positive relationship with purchase decisions. Additionally, trust weakens the positive influence of digital marketing on purchase decisions.